Estimation of electric fields in HVDC overhead lines for the future interconnection between Peru and Chile - Vilcahuaman-Sanabria, Raul; Millan-Montalvo, Oner; Lozano-Flores, Fabricio; Prado-Zuta, Piero; Tabacchi-Murillo, Jesus; Vallejos-Zuta, Alex; Solis-Farfan, Roberto (LACCEI, 2024)
The objective of this research article is a simulation to measure the magnitude of electric fields, resistive losses and the corona effect, through the development of a set of numerical formulations in Comsol and a mathematical model in Matlab, generated around a transmission line 500KV HVDC. To carry out this simulation, the Comsol software was first used jointly, which considered the types of conductors, tension level, some beam geometries and a 2D model of the tower as a transmission line; and secondly, the Matlab software, where commands were used that are organized into groups of both input and output codes accompanied by the main factors that influence the generation of said losses. To carry out this research, articles from the IEEE, CIGRE, EPRI, among the main ones, were used. Therefore, these scientific contributions that help develop the technological system of the HVDC transmission system are of utmost importance.